Occupation and bladder cancer in Boston, USA, Manchester, UK, and Nagoya, Japan. Issue 4 (December 1985) - Morrison, A S; Ahlbom, A; Verhoek, W G; Aoki, K; Leck, I; Ohno, Y; Obata, K
Abstract : Relations between occupational history and the development of cancer of the lower urinary tract ("bladder cancer") were evaluated in Boston, Massachusetts, USA, Manchester, UK, and Nagoya, Japan. Population-based series of incident cases and controls were identified and interviewed in each area. The present analysis was limited to men and was based on 430 cases and 397 controls in Boston, 399 cases and 493 controls in Manchester, and 226 cases and 443 controls in Nagoya. In Boston, elevated risk of bladder cancer was associated with employment related to dyes (relative risk = 2 X 1; 90% confidence interval, 0 X 9-5 X 1), leather (1 X 7; 1 X 1-2 X 6), paint (1 X 5; 0 X 9-2 X 4), or organic chemicals (1 X 6; 1 X 1-2 X 5). In Manchester, elevated risk was associated with 0 X 9-3 X 6). No clear association was observed between occupation and risk in Nagoya. Elevations in risk related to occupation generally were stronger in men under 65 years of age compared to older men. Differences from place to place in associations between occupation and risk may be the result of differences in the exposures to hazardous agents that jobs with the same title involve.